2022
DOI: 10.5468/ogs.22079
|View full text |Cite
|
Sign up to set email alerts
|

Improving body image and sexual life among postpartum women: a single-blind-randomized controlled trial to evaluate a social network-based cognitive-behavioral intervention

Abstract: Objective: To determine the effect of a social network-based cognitive-behavioral intervention on postpartum body image and sexual life of primiparous women. Methods:In this single-blind randomized controlled trial, 82 postpartum women were allocated into 2 intervention and control groups (allocation ratio, 1:1) using permuted block randomization. Primary outcome was change in body image scores between the groups over time. Secondary outcomes were genital self-image, sexual quality of life, and sexual satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Qualitative studies highlighted a relationship between body image concerns and sexual functioning [ 42 , 140 , 141 , 172 , 185 , 186 , 193 , 194 ]. This evidence is replicated in studies employing objective psychometric measurements [ 62 , 172 , 195 , 196 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies highlighted a relationship between body image concerns and sexual functioning [ 42 , 140 , 141 , 172 , 185 , 186 , 193 , 194 ]. This evidence is replicated in studies employing objective psychometric measurements [ 62 , 172 , 195 , 196 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 14 studies utilized the Multidimensional Body-Self Relations Questionnaire Appearance Scales—MBSRQ in healthy pregnant women, and were also excluded for similar concerns [ 36 ]. These studies employed various versions of the scale: three studies used a 34-item version [ 37 39 ], one study used a 14-item version [ 40 ], another used a 46-item version [ 41 ], one study used a 68-item version [ 42 ], one study used a 69-item version [ 43 ], and two studies used a 7-item version [ 44 , 45 ]. Furthermore, five studies utilized a 9-item version based on the BASS subscale, but data on mean sum scores and standard deviation was unavailable for two of these studies [ 46 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…People with a more positive body perception felt more sexually attractive and showed better sexual behavior [ 25 ]. On the other hand, Talebi et al [ 26 ] and Sabaghian et al [ 27 ] showed that psychological training did not have an influential role in body satisfaction. They believed that the difference in the results of the studies was because of the type of training approach, content, and intervention implementation quality.…”
Section: Discussionmentioning
confidence: 99%